Analysis of the Negative Impact of Electoral Policies on The Geometric and Global Economy - Cut Nova Rianda; Mukhsinuddin Mukhsinuddin (Teunuleh Publisher, 2026)
This study examines the multidimensional impacts of electoral policies on geometric economy models and global stability through a qualitative literature review approach. The analysis reveals that political uncertainty during election cycles significantly disrupts geometric growth consistency, with a 1–2% decline in growth ratio (r) leading to an annual GDP loss of 0.3–0.5%. Money politics systematically distorts optimal resource allocation, diverting up to 40% of budgets to non-productive activities and reducing the marginal productivity of capital (MPK) by 0.8–1.2%. Financial market volatility, particularly in the Indonesia Stock Exchange (IDX) and rupiah exchange rates, follows election-related fluctuation patterns, though mitigated by Bank Indonesia's interest rate stabilization and foreign reserve interventions. Globally, political instability in strategic nations disrupts supply chains and international trade. Sectors with exponential growth characteristics, such as technology, experience greater disruptions compared to linearly growing sectors like agriculture. The study recommends campaign financing reforms, monetary-fiscal policy coordination, and public education to minimize electoral disruptions to geometric economic models and global stability. These findings underscore the need for evidence-based policies to balance democratic processes with sustainable economic growth.